A novel method of culturing human oral mucosal epithelial cell sheet using post-mitotic human dermal fibroblast feeder cells and modified keratinocyte culture medium for ocular surface reconstruction. Issue 9 (10th June 2010) - Oie, Yoshinori; Hayashi, Ryuhei; Takagi, Ryo; Yamato, Masayuki; Takayanagi, Hiroshi; Tano, Yasuo; Nishida, Kohji
Abstract : Background/aims: To cultivate human oral mucosal epithelial cell sheets with post-mitotic human dermal fibroblast feeder cells and modified keratinocyte culture medium for ocular surface reconstruction. Methods: Human oral mucosal epithelial cells obtained from three healthy volunteers were cultured with x-ray-treated dermal fibroblasts (fibroblast group) and NIH/3T3 feeder layers (3T3 group) on temperature-responsive culture dishes. Media were supplemented using clinically approved products. Colony-forming efficiency was determined in both groups. Histological and immunohistochemical analyses were performed for cell sheets. Cell viability and purity of cell sheets were evaluated by flow cytometry. Results: Colony-forming efficiency in the fibroblast group was similar to that in the 3T3 group. All cell sheets were well stratified and harvested successfully. The expression patterns of keratin 1, 3/76, 4, 10, 12, 13, 15, ZO-1 and MUC16 were equivalent in both groups. The percentage of p63-positive cells in the fibroblast group (46.1±4.2%) was significantly higher than that in the 3T3 group (30.7±7.6%) (p=0.038, t test). The cell viability and purity were similar between the two groups. Conclusion: This novel culture method using dermal fibroblasts and pharmaceutical agents provides a safe cell processing system without xenogenic feeder cells for ocular surface reconstruction.